The Development of Islamic Context Learning Materials to Facilitate the Conceptual Understanding of Mathematics - Novikasari, Ifada; Ulpah, Maria (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
This research was conducted to develop and produce Islamic context-based mathematic learning material. The presentation of Islamic context for pre-service mathematics teachers was intended to facilitate conceptual understanding. This learning material contains rank and root, ratio and scale, and material for flat shapes and spatial shapes. The material is included in the Mathematics Materials Study course for Junior Secondary Education in the Mathematics Teacher Education program. The method in this study uses design research with the type of development study with a qualitative approach. The research phases include the preliminary research phase, the development or prototyping phase, and the assessment phase. The data were collected by filling out a learning material scoring scale by Education and Language expert and an Islamic Study expert. The quality criteria for learning material have valid results if the experts score it with excellent and valid categories. Thus, they do not need significant revision. Based on the research results, the quality of Islamic context-based mathematics learning material is classified into valid criteria at a percentage of 84% according to Mathematics Education experts and a percentage of 83.3% according to Education and Language experts and classified as an excellent category at a percentage of 94% according to Islamic Study expert. Based on these results, the product of Islamic contextual mathematics teaching materials is suitable for use in mathematics lectures.